Coping Strategies of High School Students in Flood-Prone Areas: A Study of Adaptive and Maladaptive Behaviors in Labakkang, Pangkep Regency - Syamsu Kamaruddin (Fakultas Sastra - Universitas Muslim Indonesia, 2024)
Flooding is a recurrent natural disaster that significantly impacts the lives of communities, including high school students in Labakkang, Pangkep Regency, Indonesia. This study investigates the coping strategies employed by these students to manage the challenges posed by frequent flooding. Using a quantitative survey approach, data were collected from 115 students through structured questionnaires and analyzed using frequency tabulation. The results reveal a nuanced coping behavior among the students, categorized into problem-focused and emotion-focused strategies. Problem-focused strategies, such as planning, problem-solving, and decision-making, were highly prevalent, indicating a proactive approach to mitigating the effects of flooding. Emotion-focused strategies, including acceptance, relaxation, and cognitive reframing, were also widely adopted, reflecting the students' emotional resilience and ability to manage stress. Despite these adaptive strategies, a significant reliance on avoidance behaviors was observed, suggesting an area for intervention. Avoidance, while providing temporary relief, is often considered maladaptive as it may hinder long-term problem resolution and emotional adjustment. This finding highlights the need for targeted educational and psychological interventions to promote more effective coping mechanisms. The study sheds light on the importance of integrating disaster preparedness programs into the educational curriculum, emphasizing skill development in adaptive strategies such as resource management, negotiation, and mindfulness. These findings align with established theories on stress and coping, particularly the transactional model, and provide practical insights for policymakers, educators, and mental health professionals. By addressing the gaps in coping strategies, this research contributes to enhancing the resilience and well-being of students in disaster-prone regions.